Signet-Ring Cell Carcinoma Co-Existing with Adenocarcinoma of the Ampulla of Vater. A Case Report - Maekawa, Hiroshi; Sakurada, Mutsumi; Orita, Hajime; Sato, Koichi (JOP. Journal of the Pancreas, 2011)
Context We report a case of signet-ring cell carcinoma admixed with adenocarcinoma of the ampulla of Vater. Signet-ring cell carcinoma of the ampulla of Vater is rarely encountered in clinical practice. Case report A 78-year-old man was admitted to our hospital with jaundice. Computed tomography demonstrated dilatation of the biliary tract and an enhanced mass lesion measuring 1.5 cm in the pancreatic head. Endoscopic examination showed a reddish swollen papilla of Vater, and the pathological findings on a biopsy from the papilla suggested signet-ring cell carcinoma. A pancreaticoduodenectomy was performed with a diagnosis of carcinoma of the ampulla of Vater. Postoperative pathological examination showed that the tumor was composed of signet-ring cell carcinoma and tubular adenocarcinoma. The signet-ring cell carcinoma had infiltrated to the duodenal wall and pancreatic parenchyma. Both the signet-ring cell carcinoma and the adenocarcinoma were positive on immunohistochemical staining with 45M1. Conclusion Several cases of signet-ring cell carcinoma of the ampulla of Vater have previously been reported. In our case, the histological origin of both signet-ring cell and adenocarcinoma was hypothesized to have been pancreaticobiliary epithelial cells. Image: Immunohistochemical findings for CK7.